Cephalometric evaluation of surgical mandibular advancement - Boeck, Eloisa Marcantonio; Kuramae, Mayury; Lunardi, Nadia; dos Santos-Pinto, Ary [UNESP]; Mazzonetto, Renato (FapUNIFESP (SciELO), 2010)
The treatment of Class II adult individuals with mandibular deficiency has been the combination of orthodontic treatment and orthognathic surgery. Therefore, a study was conducted in which cephalometric analysis was used to evaluate the influence of dentoalveolar decompensation in Class II patients submitted to orthodontic and surgical treatment for mandibular advancement, by bilateral osteotomy of the mandibular ramus. A sample of 15 leukoderma adult female patients were selected and three cephalometric radiographs of each patient, taken before the orthodontic treatment, before surgery and after at least 6 months postoperatively, were analyzed in a total of 45 roentgenograms. The tracings were made by the manual method and the points were digitalized using software. The results showed that values of SNB increased from 75.6 to 78.6°. The measures BNP and PGNP were reduced from -12.7 to -7.7 mm and -12.7 to -6.6 mm, respectively. For ANB there was a reduction of 3.23° (from 8.1° to 4.9°). Likewise, the values of AOBO were diminished by 6.3 mm (from 7.6 to 1.3 mm), and in the values of OJ there was a reduction of 5.7 mm (from 9 to 3.3 mm). It was concluded that the pre-surgical orthodontic treatment promoted minimal and variable dental and skeletal changes in the final result. The surgical treatment caused significant skeletal changes, especially in the measurements related to the mandible (SNB, BNP, PGNP and SNPM) or indirectly to it (ANB, AOBO and OJ).
Keywords: Mandibular advancement; Orthodontics; Retrognathism; adult; analysis of variance; cephalometry; female; histology; human; image processing; malocclusion; mandible; mandible reconstruction; methodology; orthodontics; orthognathic surgery; radiography; retrognathia; statistical model; treatment outcome; Adult; Analysis of Variance; Cephalometry; Female; Humans; Image Processing, Computer-Assisted; Linear Models; Malocclusion, Angle Class II; Mandible; Mandibular Advancement; Orthognathic Surgical Procedures; Treatment Outcome